2022
DOI: 10.1155/2022/1149000
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mechanism and Control Technology of Asymmetric Floor Heave in a Deep Soft Rock Main Roadway

Abstract: Considering the serious asymmetric deformation and failure of the floor of 1# main roadway in Wanglou Coal Mine, the mechanism of roadway asymmetric floor heave was studied through on-site investigation, theoretical analysis, numerical simulation, and on-site test. The following conclusions were drawn: (1) the floor heave of 1# main roadway is mainly caused by high original rock stress, surrounding rock stress, water physical effect, support strength, etc. (2) A mechanical model of asymmetric floor heave is bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…He Fulian et al conducted a study on the mechanism of asymmetric floor bulge in roadways. They concluded that the primary factors contributing to the main roadway floor bulge are plateau rock stress, surrounding rock stress, water action, and support strength [10]. Liu Weitao et al derived the far-field stress solution and the elastic solution for stress and deformation of the roadway surroundings under the influence of mining in the bottom slab roadway based on elastic theory [11].…”
Section: Introductionmentioning
confidence: 99%
“…He Fulian et al conducted a study on the mechanism of asymmetric floor bulge in roadways. They concluded that the primary factors contributing to the main roadway floor bulge are plateau rock stress, surrounding rock stress, water action, and support strength [10]. Liu Weitao et al derived the far-field stress solution and the elastic solution for stress and deformation of the roadway surroundings under the influence of mining in the bottom slab roadway based on elastic theory [11].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al revealed that a bolt and shotcrete support could only provide limited support strength in deep softrock roadways; moreover, bolts were generally arranged in seriously broken surrounding rock, which could hardly form a stable and effective bearing structure, leading to bearing capacity failure and serious deformation [14]. He et al established a mechanical model of asymmetric floor heave for deep soft-rock roadways, and found that the stability of the roadway floor was correlated with the stress concentration coefficient of the roadway rib, the buried depth of the roadway and the cohesion and internal friction angle of the floor rock [15]. Li et al believed that the ground stress, mining stress, and rock mass structure were the main factors affecting deep roadway deformation, and summarized the mechanism of roadway deformation and damage into the oblique pressure model, the roof bending model, the floor heave model, and the sidewall bulking model [16].…”
Section: Introductionmentioning
confidence: 99%
“…The methodologies of the studies involve laboratory studies [4][5][6][7], numerical modeling [5,[8][9][10], theoretical studies [2,8,[10][11][12][13], and site investigations [14]. Shigekazu et al [4] conducted model experiments and numerical analysis to evaluate the uplift phenomena of expressway tunnels and created three load levels for the model.…”
Section: Introductionmentioning
confidence: 99%